Pengaruh Penggunaan Media Video Terhadap Hasil Belajar Mata Pelajaran Ipa Pada Program Kesetaraan Paket B - Silfia Pratiwi; Syur'aini Syur'aini (Jurnal Family Education, 2022)
The background of this research is the lack of activeness of students in learning science subjects in the Package B Equivalence Program because the media used by tutors does not vary. This results in low student learning outcomes. This study aims to describe student learning outcomes by applying video media to science subjects and to see the effect of applying video media to learning outcomes in the Package B Equivalence Program. The approach used in this research is a quantitative experimental type with a posttest-only control group model. . All students of the Package B Equivalence Program at PKBM Sentosa Hati class IX became the population in this study. The samples were taken using simple random sampling technique from class IXA and IXB. Researchers collect data using tests. Data analysis using t-test technique. The results of this study are: 1) the learning outcomes of students who do not use video media have a low average; 2) the learning outcomes of students who were given video media treatment had a high average; and 3) there is a significant effect between the use of video media on the learning outcomes of students' science subjects in the Package B Equivalence Program